2014
DOI: 10.1186/1471-244x-14-10
|View full text |Cite
|
Sign up to set email alerts
|

Excess risk of chronic physical conditions associated with depression and anxiety

Abstract: BackgroundDepression and anxiety have been reported to be associated with chronic physical conditions. We examined the excess risk of chronic physical conditions associated with depression and/or anxiety within a multivariate framework controlling for demographic and modifiable lifestyle risk factors.MethodsWe used a retrospective cross-sectional study design. Study participants were adults aged 22–64 years from 2007 and 2009 Medical Expenditure Panel Survey. We defined presence of depression-anxiety based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 60 publications
2
70
0
4
Order By: Relevance
“…Finally, a growing body of evidence suggests that SHS exposure is associated with adverse health effects, including heart disease, cancer and a worsening of asthma, and many others (Mackay D et al, 2010;Öberg et al, 2011). All of these adverse health conditions are also associated with depression (Bhattacharya et al, 2014). Thus, SHS exposure may have effect on depressive symptoms by a direct and indirect multi-step process.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, a growing body of evidence suggests that SHS exposure is associated with adverse health effects, including heart disease, cancer and a worsening of asthma, and many others (Mackay D et al, 2010;Öberg et al, 2011). All of these adverse health conditions are also associated with depression (Bhattacharya et al, 2014). Thus, SHS exposure may have effect on depressive symptoms by a direct and indirect multi-step process.…”
Section: Discussionmentioning
confidence: 97%
“…These results suggest that the long-term sequelae of stress—rather than its immediate effects—may be critical determinants of risk for stress-related psychological disorders. Further, given the increased risk for stress-related psychopathologies in women (Solomon and Herman, 2009), as well as the increased propensity to develop psychopathology following multiple life stressors (Risch et al, 2009, Lian et al, 2014), elucidating the mechanisms underlying sex differences in recovery patterns from chronic stress has important implications for developing targeted treatment options for these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Further, there is evidence that the number of self-reported stressful life events is positively correlated with risk for depression (Risch et al, 2009) and PTSD (Lian et al, 2014), and alterations in prefrontal cortex volume are observed following repeated stressors, even in non-patient populations (Papagni et al, 2011). Thus, incomplete or aberrant recovery from stress may leave some individuals vulnerable to the deleterious effects of subsequent stressors.…”
Section: Introductionmentioning
confidence: 99%
“…However, the extent to which diabetes was associated with comorbid anxiety and depressive symptoms relative to anxiety or depressive symptoms alone was not estimated. Additionally, population-based cross-sectional evidence [25] suggests that having both a medicallydiagnosed anxiety disorder and depressive disorder was associated with the greatest risk diabetes, compared with having only one or neither condition. The assessments of depression and anxiety, however, were restricted to medical diagnoses, and the use of medical diagnoses can limit the generalizability of the findings given that undiagnosed depression and anxiety is common in both the general population [26] and in individuals with diabetes [27].…”
Section: Introductionmentioning
confidence: 96%